Вдосконалення методів управління виробництвом за рахунок використання алгоритму кажанів - Грибков, Сергій Віталійович; Сєдих, Ольга Леонідівна (My University, 2020)
Робота присвячена вдосконаленню системи управління харчовим виробництвом на прикладі молокозаводу з використання сучасних алгоритмів та інформаційних технологій. У роботі розглянуто багатокритеріальну задачу управління виробництвом та запропоновано розв’язання задачі планування виконання замовлень як багатокритеріальної задачі прийняття рішень на основі мета-евристичних алгоритмів. В роботі розглядаються модифікації алгоритму та їх застосування. The work is devoted to the improvement of the food production management system on the example of a dairy plant using modern algorithms and information technologies. The paper considers the multicriteria problem of production management and proposes the solution of the problem of planning the execution of orders as a multicriteria problem of decision making based on meta-heuristic algorithms. Modifications of the algorithm and their application are considered in the work. The analysis of literary sources is carried out. The mathematical model proposed by the authors in previous works is highlighted. The Paretto approach is considered, and its anecdotes are highlighted. The algorithm and its modifications are investigated. A study on the application of the bat algorithm and its modifications was conducted. Based on the results of comparison of the considered algorithms, the use of the bat algorithm based on the reduction factor is proposed. The bat's algorithm based on the reduction factor proves its effectiveness as a random search method. The disadvantages of this method include a large number of free parameters, the value of which often depends on the result, on the other hand, there is no reason to choose these values. The considered methods will be included as a separate module in DSS for food production management of the enterprise.
Keywords: алгоритм; молокозавод; алгоритм кажанів; algorithm; dairy plant; bat algorithm; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки